1999
DOI: 10.1302/0301-620x.81b4.0810686
|View full text |Cite
|
Sign up to set email alerts
|

Does thrombophilia play an aetiological role in Legg-Calvé-Perthes disease?

Abstract: H eritable thrombophilic disorders have been proposed as one of the causes for Legg-Calvé-Perthes disease. A total of 62 patients diagnosed with this disease between 1988 and 1997 and 50 controls were screened for thrombophilia. The incidence and relationship of thrombophilia to the severity of the disease were evaluated.One patient and none of the controls had protein S deficiency. One of the control group and one of the patients had protein C deficiency with the latter child also having a combined deficiency… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…Our findings did not reveal significant factor deficiencies or levels of APC-R (5.8%) and are in keeping with more recent studies. 16,17 The only report which has commented previously on the APTT was that by Hayek et al, 16 who demonstrated no abnormalities. The APTT was part of the basic coagulation profile carried out in this study.…”
Section: Discussionmentioning
confidence: 97%
“…Our findings did not reveal significant factor deficiencies or levels of APC-R (5.8%) and are in keeping with more recent studies. 16,17 The only report which has commented previously on the APTT was that by Hayek et al, 16 who demonstrated no abnormalities. The APTT was part of the basic coagulation profile carried out in this study.…”
Section: Discussionmentioning
confidence: 97%
“…The proposed mechanism is that microthrombi would lodge in the vessels that nourish the femur, blocking the supply of blood, which would cause the characteristic necrosis of LCPD [15,16]. Results in multiple studies have supported this theory; however, the lack of reproducibility in these results has given rise to controversies as to whether hemostasis is involved in the development and suffering of LCPD (12,(17)(18)(19)(20).…”
Section: Discussionmentioning
confidence: 99%
“…However, there are weak associations to a range of thrombophilic traits and LCPD, with findings that are far from being consistent. 48,49 So, studies of coagulopathy appear to exclude a major association. The etiological factor responsible for causation of LCPD, therefore, remains elusive.…”
Section: Etiological Hypothesesmentioning
confidence: 99%